2002
DOI: 10.1002/hipo.10099
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term potentiation as a substrate for memory: Evidence from studies of amygdaloid plasticity and Pavlovian fear conditioning

Abstract: ABSTRACT:Recent reports have raised concerns about the ability of long-term potentiation (LTP) to account for associative learning and memory. In this paper, we review the many mechanistic similarities between one form of associative learning, Pavlovian fear conditioning, and amygdaloid LTP. We then address many of the criticisms levied against LTP within the framework of fear conditioning. We believe that many of the apparent discrepancies between LTP and behavior can be generally accounted for by a failure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(51 citation statements)
references
References 130 publications
(137 reference statements)
2
49
0
Order By: Relevance
“…The data described above suggest how the amygdaloid fear circuit might come under inhibitory control after extinction, but they do not explain the contextual modulation of extinction. The hippocampus has extensive reciprocal projections with the amygdala (Pitkanen et al 2000), and hippocampal projections to the amygdala exhibit synaptic plasticity (Maren and Fanselow 1995;Goosens and Maren 2002). Hence, the context-dependence of extinction may arise from an integration of contextual representations processed in the hippocampus and excitatory and inhibitory CS-US associations processed in the lateral amygdala.…”
Section: Discussionmentioning
confidence: 99%
“…The data described above suggest how the amygdaloid fear circuit might come under inhibitory control after extinction, but they do not explain the contextual modulation of extinction. The hippocampus has extensive reciprocal projections with the amygdala (Pitkanen et al 2000), and hippocampal projections to the amygdala exhibit synaptic plasticity (Maren and Fanselow 1995;Goosens and Maren 2002). Hence, the context-dependence of extinction may arise from an integration of contextual representations processed in the hippocampus and excitatory and inhibitory CS-US associations processed in the lateral amygdala.…”
Section: Discussionmentioning
confidence: 99%
“…Also, blockade of benzodiazepine sites or lesions of the BLA attenuate the anxiolytic influence of systemic benzodiazepines (Sanders and Shekhar, 1991). Furthermore, Goosens and Maren (2002) suggested that the BLA is able to retain aspects of fear memories even in the absence of the CeA. Shors and Mathew (1998) demonstrated a selective role of the BLA in the facilitating influence of stress on classical eyeblink conditioning.…”
Section: Discussionmentioning
confidence: 99%
“…Similar training procedures can be used in laboratory animals and human volunteers and current data suggest a large degree of similarity in neural mechanisms across species. A number of excellent recent reviews are available providing more detailed treatment of various aspects of the anatomy, physiology, and molecular biology of FC than space here permits (e.g., Blair, et al, 2001;Davis, 2000;Fanselow & Poulos, 2005;Goosens & Maren, 2002;Kim & Jung, 2006;Maren 2000;Medina, et al, 2002;Pare, Quirk & LeDoux, 2004;Stork & Pape, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Electrophysiological studies have shown that unit responses in BLA are consistent with processing relevant presynaptic inputs and appropriate stimulation regiments result in long-term potentiation (LTP) at BLA synapses both in vitro and in vivo. Because of the large amount of systematic work being done on this region of the amygdala, a clear and detailed picture of the molecular and cellular events underlying FC-related synaptic plasticity in this structure is emerging (Blair, et al, 2001;Goosens & Maren, 2002;Maren & Quirk, 2004) While the BLA is thought by many to be a site of critical synaptic plasticity in FC, the expression of fear-related conditional responses (CR) during subsequent behavioral performance based on this learning is thought to depend on intrinsic amygdaloid connections from BLA to the central nucleus (CeA) and from there to a widespread series of target structures more specifically involved in the generation of particular behavioral and physiological elements of the fear response. Expression of FC involves multiple simultaneous outputs and systems-level analyses have identified various unique contributions to components of this response.…”
Section: Introductionmentioning
confidence: 99%